PELAKSANAAN PENGAWASAN OLEH ATASAN LANGSUNG DI DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI SUMATERA BARAT - Ade Kurnia Kusuma; Syahril Syahril; Ahmad Sabandi (Jurnal Bahana Manajemen Pendidikan, 2019)
The aim of this study in general is to get a general description of the implementation of supervision by direct superiors at the Department of Industry and Commerse of West Sumatra. While the specific aim of this study is to get an overview of the implementation of supervision by direct supervisors seen from aspects: standard setting, supervision techniques, time of supervision, assessment and follow-up at the Department of Industry and Commerse of West Sumatra. This research is descriptive research. The population of this research is 116 employees of the Department of Industry and Trade of West Sumatra Province. While the sample in this study uses the Slovin formula, which is 56 people. The data collection tool in this study is a questionnaire, which is arranged in the form of a Likert scale that has been tested for validity and reliability. Data is analyzed by using the mean formula. The results of the study show that: the standard setting by direct superiors has illustrated a fairly good supervision with an average score of 2.9; supervision techniques by direct superiors have illustrated fairly good supervision with an average score of 3.3; the time of supervision by direct superiors has described good supervision with an average score of 3.8; the appraisal by direct supervisors at the has described a fairly good supervision with an average score of 3.3; follow-up by direct supervisors has described good supervision with an average score of 3.8. Overall, the implementation of supervision by direct superiors at the Department of Industry and Commerse of West Sumatra has illustrated a fairly good supervision.